External validation of the simple NULL-PLEASE clinical score in predicting outcomes of out-of-hospital cardiac arrest in the Danish population - a nationwide register-based study. (2nd May 2022) - Byrne, C; Barcella, CA; Krogager, ML; Pareek, M; Ringgren, KB; Wissenberg, M; Folke, F; Gislason, G; Koeber, L; Lippert, F; Torp-Pedersen, C; Kragholm, KH; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The Danish Heart Foundation The Danish Foundation TrygFonden Background: Clinical decision-making in patients with out-of-hospital cardiac arrest (OHCA) admitted to the hospital is challenging, and multiple scoring systems have been developed to predict survival. The NULL-PLEASE score (Nonshockable rhythm, Unwitnessed arrest, Long no-flow or Long low-flow period, blood pH <7.2, Lactate >7.0 mmol/L, End-stage renal disease on dialysis, Age ≥85 years, Still resuscitation, and Extracardiac cause) may be able to identify patients with OHCA who are unlikely to survive; however, this score system have not previously been tested in a nationwide setting. Purpose: The aim of this study was to validate the NULL-PLEASE clinical score to identify patients with OHCA in the Danish population who are unlikely to survive. Methods: We retrospectively validated the predictive ability of the NULL-PLEASE score, using Danish nationwide registry data from 2001-2015. We identified OHCA survivors who had return of spontaneous circulation (ROSC) or ongoing cardiopulmonary resuscitation at hospital arrival and all NULL-PLEASE score parameters available. The primary outcome was 1-day mortality, and the secondary outcome was 30-day mortality. Outcomes were estimated using multivariable logistic regression with a NULL-PLEASE score of zero as reference. Results: A total of 868 patients with all NULL-PLEASE score parameters available was included in the analysis. Overall, 1-day mortality was 33%, and 30-day mortality was 62%. A NULL-PLEASE score >0 (assessed as a continuous variable) was associated with significantly increased 1-day mortality (odds ratio (OR): 1.62, 95% confidence interval (CI): 1.51-1.74) as well as significantly increased 30-day mortality (OR: 1.80, 95% CI: 1.66-1.96). Figures 1 and 2 show the ROC curves of NULL-PLEASE and 1-day mortality and 30-day mortality, respectively. Area under the curve (AUC) for 1-day mortality was 0.81, and AUC for 30-day mortality was 0.83. Assessed categorically, a NULL-PLEASE score ≥5 was associated with a particularly high OR for mortality: 1-day mortality (OR: 7.46, 95% CI: 5.42-10.27), and 30-day mortality (OR: 10.596, 95% CI: 7.32-15.33). Conclusions: In a large nationwide OHCA-cohort, we found that a NULL-PLEASE score >0 was associated with higher 1-day mortality as well as higher 30-day mortality.